Business Process and Service Change Management in Service Oriented Virtual Organizations - Obidallah, Waeal (Université d'Ottawa / University of Ottawa, 2013)
Service Oriented Virtual Organizations (SOVOs) business processes and services are subject to change to meet the internal and external requirements of the competitive, complex and rapidly changing environment they operate in. More practical and efficient ways of change management are needed to allow different partners to initiate changes to their business process and services in a faster and user-transparent manner. This thesis proposes a Change Management Framework for service oriented virtual organizations including a structural and a procedural framework. The structural framework categorizes changes in the SOVO into three layers of change; which include the value network layer, the collaborative process layer and the service providers’ layer, and identifies the impact of change on each layer. Furthermore, the structural framework identifies various triggers of changes which eventually lead to actions taken at the three layers. The change management procedural framework is derived from the ITIL V3, ECM and ECOLEAD best practices and recommendations, customized to fit the SOVO change requirements. It provides different components including the six layers for change processes, change control, change actors and related management processes. The change management procedural framework provides a sequence of steps and methods that the SOVO and its participated organizations can follow in initiating changes to their business processes or services. We design an implementation architecture and a prototype for building the change management console which enables the SOVO change management participants to initiate, assess, collaborate, monitor and authorize changes. The prototype is developed to realize and validate the change management process of change in the SOVO environment. We employ the various capabilities of the IBM Business Process Management (BPM) (including its recent Web 2.0 capabilities) to increase the collaboration between partners in the process of change. We demonstrate that the proposed solutions facilitate and enhance the process of change by effectively engaging the SOVO partners in the process of change.
Keywords: Virtual Organization; Service Oriented Virtual Organization; Change Management; Change Classification; Change Triggers; Change processes